Factors associated with psychic symptomatology in diabetics during the COVID-19 pandemic - Souza,Gustavo Fonseca de Albuquerque (2021)
Abstract Objectives: to determine the frequency and factors associated with severe / extreme signs and symptoms of stress, anxiety and depression in diabetic patients during the COVID-19 pandemic. Methods: cross-sectional study conducted in April /May 2020, which included 162 individuals with diabetes mellitus and over 18 years old. An online questionnaire was applied on social networks, composed of biological, sociodemographic, clinical characteristics and the Stress, Anxiety and Depression Scale (DASS-21). For statistical analysis, a multivariate logistic regression model was applied with a 5% significance level. Results: frequency of 37.7%, 43.3% and 45.1% were found for some symptom of stress, anxiety and depression, respectively. The factors associated with sign and symptoms of severe / extreme psychic disorders were: not having religion (stress, anxiety and depression); be at graduation (stress and anxiety); history of anxiety and depression (anxiety and depression); not practicing or decreasing physical exercises and starting, increased or continue taking sleeping medications (stress); history of contact with a suspected case of COVID-19, absence or decreased leisure (anxiety); female gender, absence of a partner, decreased family income and work or study (depression). Conclusion: the frequency of psychological disorders was higher than described in the literature on diabetic patients, being associated with biological, sociodemographic, clinical factors and aspects related to COVID-19 during the pandemic